Coprecipitation technique to prepare ZnM2O6 powders - Deshpande, V. V.; Patil, M. M.; Navale, S. C.; Ravi, V. (Bulletin of Materials Science, 2005)
A simple coprecipitation technique was successfully applied for the preparation of pure ultrafine single phase, ZnNb2O6 (ZN). Ammonium hydroxide was used to precipitate Zn2+ and Nb5+ cations as hydroxides simultaneously. This precursor on heating at 750 degrees, produced ZN powders. For comparison, ZN powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology were studied by transmission electron spectroscopy (TEM).
Keywords: Ceramics; Electron microscopy; electronic materials; X-ray diffraction

Synthesis of bismuth oxide nanoparticles at 100 degrees C - Patil, M. M.; Deshpande, V. V.; Dhage, S. R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of ultrafine Bi2O3 particles at 80-100 degrees C under refluxing conditions. Freshly prepared bismuth hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 6-12 h. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. The thermal decomposition of bismuth hydroxide yields Bi2O3 only at 400 degrees C. This shows the advantage of the present method. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these oven-dried powders. (c) 2005 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of bismuth oxide nanoparticles by citrate gel method - Anilkumar, Mettu; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and citric acid solution is taken in 1: 1 molar ratio and heated on hot water bath. A gel is formed on evaporation of the water, which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nanocrystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Electron microscopy; powders : chemical preparation; X-ray methods

Synthesis of bismuth oxide nanoparticles using bismuth nitrate and urea - Jha, Ratnesh Kumar; Pasricha, R.; Ravi, V. (Ceramics International, 2005)
A mixture of bismuth nitrate and urea is taken in 1:5 molar ratio and heated on hot water bath. A precipitate is formed on evaporation of the water which on decomposition at 400 degrees C produces nanocrystalline Bi2O3 particles. Formation of nano crystallites of Bi2O3 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscopy (TEM) investigations revealed for these powders an average particle size of 50 nm. (c) 2004 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: calcination; Electron microscopy; X-ray methods

Synthesis of Ce0.75Zr0.25O2 at 100 degrees C - Dhage, S. R.; Gaikwad, S. R.; Muthukumar, P.; Ravi, V. (Ceramics International, 2005)
A simple gel to crystal conversion route has been used for the preparation of Ce0.75Zr0.25O2 phase at 80-100degreesC under refluxing conditions. Freshly prepared metal hydroxides gel from cerium and zirconium salt solution is allowed to crystallize under refluxing and stirring conditions for 4-10 h. Formation of nano crystallites of Ce0.75Zr0.25O2 is confirmed by X-ray diffraction (XRD). Transmission electron microscopy (TEM) investigations revealed the average particle size of these powders to be 5 nm. (C) 2004 Elsevier Ltd and Techna S.r.l. All rights reserved.
Keywords: CeO2; chemical preparation; Electron microscopy; powders; X-ray methods

Synthesis of fine particles of ZnO at 100 degrees C - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A simple gel to crystal conversion route has been followed for the preparation of fine ZnO at 80-100 degreesC under refluxing conditions. Freshly prepared zinc hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 It. Formation of fine crystallites of ZnO is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for these powders. (C) 2004 Elsevier B.V All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of nanocrystalline Mn3O4 at 100 degrees C - Anilkumar, Mettu; Ravi, V. (Materials Research Bulletin, 2005)
A simple gel to crystal conversion route has been followed for the preparation of nanocrystalline tetragonal Mn3O4 powders at 80-100 degrees C under refluxing conditions. Freshly prepared manganese hydroxide gel is allowed to crystallize under refluxing and stirring conditions for 4-6 h. Formation of nano crystallites of Mn3O4 is confirmed by X-ray diffraction (XRD) study. Transmission electron microscope (TEM) investigations revealed that the average particle size is 50 nm for these powders. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Synthesis of rutile from ATO and stearic acid - Patil, M. M.; Deshpande, V. V.; Deshpande, S. B.; Samuel, V.; Ravi, V. (Materials Letters, 2005)
Nanocrystalline titanium dioxide in the rutile phase has been obtained from the solid state reaction between ammonium titanyl oxalate (ATO) and stearic acid at 400 degrees C in air. The fine powders of ATO and stearic acid are mixed well using acetone in an agate mortar and pestle for 2 h. This mixture (weight ratio of ATO to stearic acid > 5) on heating at 400 degrees C produces rutile powders. For the ratios of ATO to stearic acid < 5, a mixture of anatase and rutile phases is obtained. Pure ATO yields anatase phase on decomposition at 400 degrees C. These powders were characterized by X-ray diffraction (XRD), BET surface area measurements and transmission electron microscopy (TEM) studies. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray techniques

Synthesis of Sr0.5Ba0.5Nb2O6 by urea method - Dhage, S. R.; Pasricha, R.; Ravi, V. (Materials Letters, 2005)
A precipitate was formed when an aqueous solution of SrCl2, BaCl2, NbF5 and urea in stoichiometric ratio (total metal cations to urea ratio is 5) is heated on a water bath.. This precipitate on decomposition at 750 degreesC yielded the nanocrystallites of ternary oxide, Sr0.5Ba0.5Nb2O6 (SBN) as confirmed by X-ray diffraction study (XRD). This is much lower temperature as compared to that prepared by traditional solid state method (1000 degreesC as reported for the formation of SBN ceramics. Transmission electron microscope (TEM) investigations revealed that the average particle size is 100 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 1050. The ferroelectric hysteresis loop parameters of these samples were also studied. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides

Chemical methods to synthesize FeTiO3 powders - Mona, J.; Kale, Sangeeta N.; Gaikwad, A. B.; Murugan, A. Vadivel; Ravi, V. (Materials Letters, 2006)
Three different techniques were used to synthesize FeTiO3 powders. The first method is simple coprecipitation of both Fe and Ti ions under basic conditions using standard ammonia solution from aqueous ferric nitrate and titanium oxy chloride. This precipitate on heating at 400 degrees C produces ilmenite phase. The second method is to digest hydroxide precipitates at 100 degrees C to form FeTiO3 phase. The third technique is to make use of citrate process to form FeTiO3 powders. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). Particle size and morphology were studied by Transmission Electron Microscopy (TEM). (c) 2005 Elsevier B.V. All tights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray methods

Coprecipitation technique to prepare Sr0.5Ba0.5Nb2O6 - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Bulletin of Materials Science, 2006)
An aqueous mixture of ammonium oxalate and ammonium hydroxide was used to coprecipitate barium and strontium ions as oxalates and niobium ions as hydroxide under basic conditions. This precursor on calcining at 750 degrees C yielded Sr0.5Ba0.5Nb2O6 phase. This is a much lower temperature than that prepared by traditional solid state method (1000 degrees C) as reported for the formation of Sr0.5Ba0.5Nb2O6 (SBN). Transmission electron microscopic (TEM) investigations revealed that the average particle size was 80 nm for the calcined powders. The room temperature dielectric constant at I kHz was found to be 1100. The ferroelectric hysteresis loop parameters of these samples were also studied.
Keywords: Ceramics; Electron microscopy; ferroelectricity; Oxides; X-ray diffraction

Phase evolution of NiTiO3 prepared by coprecipitation method - Murugan, A. Vadivel; Samuel, V.; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A simple coprecipitation technique was used for the preparation of NiTiO3 powders. Ammonium carbonate solution was added to a solution mixture containing stoichiometric amounts of Ni(NO3)(2) and TiOCl2 to precipitate nickel as carbonate and titanium as hydroxide under basic conditions. The precipitate was calcined at different temperatures ranging from 100 to 800 degrees C and phase evolution of NiTiO3 was investigated by X-ray diffraction (XRD) studies. It is observed that nickel titanate was formed at 750 degrees C. For comparison, NiTiO3 was also prepared by standard ceramic process. Particle size and morphology was studied by transmission electron microscopy (TEM). (c) 2005 Elsevier B.V. All fights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; NiTiO3; Oxides; X-ray diffraction

Preparation of nanocrystalline ferroelectric BaBi4Ti4O15 by Pechini method - Murugan, A. Vadivel; Navale, S. C.; Ravi, V. (Materials Letters, 2006)
A gel was formed when an aqueous solution of BaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 600 degrees C produced the nano crystallites of ternary oxide, BaBi4Ti4O15 (BBT). The phase contents and lattice parameters were Studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at I KHz is 90. The ferroelectric hysteresis loop parameters of these samples were also studied by a home built Sawyer-tower circuit. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: dielectric properties; Electron microscopy; ferroelectric properties; powders chemical preparation

Synthesis of MgNb2O6 by coprecipitation - Navale, S. C.; Gaikwad, A. B.; Ravi, V. (Materials Research Bulletin, 2006)
A simple coprecipitation technique was used successfully to synthesize fine powders of MgNb2O6 (MN) phase. An aqueous mixture of ammonium carbonate and ammonium hydroxide was used to precipitate Mg2+ and Nb5+ cations as carbonate and hydroxide respectively under basic conditions. This precipitate on heating at 750 degrees C produced MN powders. For comparison MN powders were prepared by the traditional solid state method. The phase content and the lattice parameters were studied by powder X-ray diffraction (XRD). Particle size and morphology of the particles were studied by scanning electron microscopy (SEM). (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Co-precipitation technique to prepare BaTa2O6 - Navale, S. C.; Samuel, Violet; Gaikwad, A. B.; Ravi, V. (Ceramics International, 2007)
A mixture of ammonium oxalate and ammonium hydroxide was used to co-precipitate barium and tantalum ions as barium oxalate and tantalum hydroxide under basic conditions. On calcination at 750 degrees C, this precursor yielded BaTa2O6 (BT) ceramics. This is much lower temperature as compared to that prepared by traditional solid-state method (1000 degrees C) as reported for the formation of BaTa206. Transmission electron microscope (TEM) investigations revealed that the average particle size is 70 nm for the calcined powders. The room temperature dielectric constant at 1 kHz is found to be 100. (c) 2005 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: barium tantalate; Ceramics; Electron microscopy; Oxides; X-ray diffraction

Coprecipitation technique to prepare NiNb2O6 - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Natarajan, N.; Ravi, V. (Materials Letter, 2007)
A mixture of ammonium carbonate and ammonium hydroxide was used to coprecipitate nickel and niobium ions as nickel carbonate and niobium hydroxide under basic conditions. This precursor yielded NiNb2O6 (NN) ceramics on calcining at 700 degrees C (at a temperature lower than 800 degrees C which is necessary for the formation of NiNb2O6 when prepared by the traditional solid state method). The average particle size and morphology of these powders were investigated by transmission electron microscope (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; Oxides; X-ray methods

Novel technique to prepare LiNbO3 at low temperature - Samuel, V.; Gaikwad, A. B.; Jadhav, A. D.; Mirji, S. A.; Ravi, V. (Materials Letter, 2007)
Fresh niobium hydroxide was first precipitated from NbF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and niobium hydroxides together and heating at a low temperature (400 degrees C) produced pure ultrafine single phase LiNbO3 (LN). In the literature, this is the lowest temperature so far reported on the formation of LN. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; LiNbO3; X-ray diffraction

Preparation of nanocrystalline ferroelectric CaBi4Ti4O15 by citrate gel method - Murugan, A. Vadivel; Gaikwad, A. B.; Samuel, V.; Ravi, V. (Ceramics International, 2007)
A gel was formed when an aqueous solution of CaCl2, BiNO3, TiOCl2 and citric acid in stoichiometric ratio is heated on a water bath. This gel on decomposition at 700 degrees C produced nano crystallites of the ternary oxide, CaBi4Ti4O15 (CBT). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). The room temperature dielectric constant at 1 kHz is 390. The ferroelectric hysteresis loop parameters of these samples were also studied by a home-built Sawyer-tower circuit. (c) 2006 Elsevier Ltd and Techna Group S.H. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Co-precipitation technique to prepare BiNbO4 powders - Radha, R.; Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique was successfully used for the preparation of pure ultrafine single phase BiNbO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. For comparison, BN powders were also prepared by the traditional solid-state method. It is observed that the co-precipitation technique produces BiNbO4 on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the solid-state method. The phase contents and lattice parameters were Studied by powder X-ray diffraction (XRD). (C) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Co-precipitation technique to prepare BiTaO4 powders - Muthurajan, H.; Gupta, U. N.; Rituraj, B.; Rao, N. Koteswara; Pradhan, Sivaram; Radha, R.; Ravi, V. (Materials Letters, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure ultrafine single phase BiTaO4. A standard ammonium hydroxide solution was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. This precursor, on heating at 600 degrees C, produced product phase. This is the lowest temperature for the formation of BiTaO4 phase so far reported in the literature. For comparison BiTaO4 powders were also prepared by the traditional solid state method. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: BiTaO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis and characterization of BiNbO4 powders - Radha, R.; Muthurajan, H.; Rao, N. Koteswara; Pradhan, Sivaram; Gupta, U. N.; Jha, Ratnesh Kumar; Mirji, S. A.; Ravi, V. (Materials Characterization, 2008)
BiNbO4 powders, a potential microwave dielectric ceramic were prepared by both coprecipitation and solid state techniques. In the former method, an aqueous ammonium hydroxide was used to precipitate Bi3+ and Ta5+ cations as hydroxides simultaneously under basic conditions. It is observed that the co-precipitation produces BiNbO4 phase on heating at 600 degrees C, whereas complete phase formation occurs only at 800 degrees C in the case of solid state method. The phase contents and lattice parameters were studied by powder X-ray diffraction. The sequence of the reaction and phase evolution of BiNbO4 were also studied by the X-ray diffraction. The samples were characterized by the differential-thermal/thermo-gravimetric analyses and scanning electron microscopy techniques. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: BiNbO4; Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Low temperature synthesis of SrNb2O6 and SrTa2O6 using hydroxide precursor - Muthurajan, H.; Kumar, H. H.; Koteswara Rao, N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Ravi, V. (Materials Letters, 2008)
SrNb2O6 (SN) or SrTA(2)O(6) (ST) compounds were prepared at low temperatures for the first time from hydroxide precursors. A simple procedure of mixing commercially purchased strontium hydroxide and niobium (or tantalum) hydroxide thoroughly together and heating at a low temperature (<400 degrees C) produced SrNb2O6 (SN) or SrTa2O6 (ST) powders. This is the lowest temperature so far reported for the formation of these phases. These materials are potential candidates for ferroelectric and electro-optic applications. The reaction sequence and evolution of the phase formation were investigated by X-ray diffraction (XRD) studies. The average particle size and morphology of these powders were studied by scanning electron microscopy (SEM). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Electron microscopy; electronic materials; X-ray diffraction

Novel hydroxide precursors for low temperature synthesis of selected ternary oxides - Muthurajan, H.; Rao, N. Koteswara; Gupta, U. N.; Pradhan, Sivaram; Jha, Ratnesh Kumar; Kumar, H. H.; Mirji, S. A.; Ravi, V. (Materials Research Bulletin, 2008)
A novel method of using hydroxide precursors to reduce the synthesis temperature for few selected ternary oxides has been presented here. This technique is very useful and advantageous when the ternary oxides contain an alkaline earth element. The selected compositions for this method are BaCeO3 (BC), BaBiO3 (BB), La0.7Sr0.3CoO3 (LSCO) and BaBi2Nb2O9 (BBN). Commercially purchased strontium (or barium) hydroxide and freshly prepared lanthanum, cobalt, bismuth and niobium hydroxides were mixed thoroughly in stoichiometric ratio and heated at different temperatures ranging from 100 to 700 degrees C for 10 h for corresponding compositions. The sequence of the reaction and evolution of the product phase were studied by the X-ray diffraction (XRD) studies. The phase purity and lattice parameters were also determined by XRD investigations. All the product phases in each case were formed at relatively low temperature than when they were prepared by co-precipitation or solid state method. The morphology and average particle size of these powders were investigated by scanning electron microscopy (SEM). (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray diffraction

Novel technique to prepare LiTaO3 at low temperature - Muthurajan, H.; Kumar, H. H.; Natarajan, N.; Ravi, V. (Ceramics International, 2008)
Firstly, fresh tantalum hydroxide was precipitated from TaF5 solution using an aqueous ammonium hydroxide under basic conditions. Then a simple procedure of mixing lithium and tantalum hydroxides together and heating at a low temperature (450 degrees C) produced pure ultrafine single phase LiTaO3 (LT). This is the lowest temperature so far reported for the formation of LT in the literature. The phase content and lattice parameters are determined by X-ray diffraction (XRD). The average particle size and morphology were studied by transmission electron microscopy (TEM). (c) 2006 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: chemical synthesis X-ray diffraction; Electron microscopy; electronic materials; LiTaO3

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Synthesis of LSMO at low temperature by novel hydroxide precursor technique - Gupta, U. N.; Muthurajan, H.; Kumar, H. H.; Rao, N. Koteswara; Gokhale, Suresh P.; Ravi, V. (Materials Letters, 2008)
A novel technique of mixing individual hydroxide is employed to prepare La0.65Sr0.35MnO3 (LSMO) at low temperature. Freshly prepared lanthanum and manganese hydroxides are mixed thoroughly with strontium hydroxide in stoichiometric ratio and heated at different temperatures ranging from 100 to 500 degrees C for 6 h. At 500 degrees C, formation of La0.65Sr0.35MnO3 was confirmed by the X-ray diffraction studies (XRD). This is the lowest temperature so far reported in the literature. The particle size and morphology were investigated by scanning electron microscopy (SEM). (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; La0.65Sr0.35MnO3; Oxides; Precipitation; X-ray diffraction